Effect of Surface Phenomena on Selective Separation Properties of Liquid Crystal Stationary Phase - Dzagania, M.; Eprikashvili, L.; Zautashvili, M.; Pirtskhalava, N.; Rubashvili, I. (Хімія, фізика та технологія поверхні, 2010)
The present work deals with the study on the distribution of contribution of adsorption and dissolution to retention volume of individual components in gas-liquid chromatography as dependent on the amount of liquid crystal stationary phase deposited on solid support and on the chromatographic column temperature. Досліджено розподіл внесків адсорбції і розчинення в утримуваний об'єм окремих компонентів у газорідинної хроматографії в залежності від кількості нанесеної на твердий носій рідкокристалічною нерухомої фази і температури нагріву хроматографічної колонки. Исследовано распределение вкладов адсорбции и растворения в удерживаемый объём отдельных компонентов в газо-жидкостной хроматографии в зависимости от количества нанесенной на твердый носитель жидкокристаллической неподвижной фазы и температуры нагрева хроматографической колонки.